2015
DOI: 10.1007/s10453-015-9385-3
|View full text |Cite
|
Sign up to set email alerts
|

Pollen calendars: a guide to common airborne pollen in Andalusia

Abstract: This paper presents pollen calendars for the capital cities of the eight provinces of Andalusia (south of Spain) based on the airborne pollen counts recorded in a 10-year historical database. Pollen calendars are useful in the prevention and diagnosis of hay fever, in that they enable the timing and severity of the pollen season to be clearly defined. The differences encountered-in terms of both pollen spectra and the length and timing of the pollen season (start date, peak date, peak concentration and end dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…These periods may represent the pollen seasons in Qatar. Generally, grass and Amaranthaceae pollen predominate in the spring period (May–June) in Southern Europe [ 31 ] and North America [ 32 ]. However, Amaranthaceae and Poaceae showed different patterns with other smaller peaks observed in late January (Amaranthaceae) and November to December (Poaceae), during the winter and cold seasons of Qatar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These periods may represent the pollen seasons in Qatar. Generally, grass and Amaranthaceae pollen predominate in the spring period (May–June) in Southern Europe [ 31 ] and North America [ 32 ]. However, Amaranthaceae and Poaceae showed different patterns with other smaller peaks observed in late January (Amaranthaceae) and November to December (Poaceae), during the winter and cold seasons of Qatar.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations in our study must be considered in the interpretation of the findings, including the duration of the aerobiological sampling (2 years). Based on differences recorded over several years of aerobiological studies in different countries, long-term samplings are recommended to better establish daily and annual patterns for the different pollen types in a locality [ 31 , 32 ]. However, 2 years were considered sufficient to provide preliminary data that could help healthcare providers to identify the commonest pollen and provide the treatment approach and the needed immunotherapy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Back-trajectory analysis showed that pollen collected prior to flowering in the PDO area apparently came from elsewhere in Andalusia, for example from Huelva and Malaga, where flowering generally takes place earlier due to the more temperate coastal climate. Previous research in woody species has highlighted an advance in flowering in these areas of Andalusia (Alcázar et al ., 2011; Martínez-Bracero et al ., 2015; Velasco-Jiménez et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to datasets obtained by Red Balear de Aeropalinología (2015) from a Hirst-type volumetric sampler (Hirst 1952) located in Alaior-Can Salord (Fig. 1) following the protocols of REA (Galán et al 2007;Martínez-Bracero et al 2015), the main atmospheric pollen assemblage is dominated by Cupressaceae, Oleaceae (Fraxinus, Olea), Pinaceae,…”
Section: Experimental Ground Stone Tools and Plant Materialsmentioning
confidence: 99%